Evaluating the effectiveness of an assessment workshop for medical teachers - Sim, J.H.; Tong, F.T.; Foong, C.C.; Vadivelu, J. (2014)

(untitled)
The University of Malaya is currently undergoing a new medical curriculum transformation which began in September 2013. lt is also the first time that ExamBank was introduced. A Hands-on Assessment Workshop was conducted to train medical teachers on writing quality single best answers questions (SBAs) and extended matching questions (EMQs) in ExamBank. This paper aims to report on the effectiveness of the workshop.